2015
DOI: 10.1111/pme.12637
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in “Probable” Vascular Dementia: Preliminary Findings

Abstract: As VaD patients may experience greater pain than controls, it is essential for prescribers to be aware of the presence of this neuropathology if these patients are to receive adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…This is the first study to relate the severity of WMH to self-reported pain intensity in patients with dementia and without dementia, limiting comparisons between studies. However, our results are in line with earlier studies of older nursing home patients with “possible” or “probable” vascular dementia who found that nursing home residents with VaD have a higher self-reported pain intensity than nursing home residents without dementia 12,13. Indeed, a similar study reported that older cognitively impaired nursing home patients with a potentially painful condition had a higher chance of reporting pain when they also suffer from diabetes or hypertension, both known risk factors for WMH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is the first study to relate the severity of WMH to self-reported pain intensity in patients with dementia and without dementia, limiting comparisons between studies. However, our results are in line with earlier studies of older nursing home patients with “possible” or “probable” vascular dementia who found that nursing home residents with VaD have a higher self-reported pain intensity than nursing home residents without dementia 12,13. Indeed, a similar study reported that older cognitively impaired nursing home patients with a potentially painful condition had a higher chance of reporting pain when they also suffer from diabetes or hypertension, both known risk factors for WMH.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with AD report a lower chronic pain intensity than individuals without dementia 811. Patients with VaD report a higher pain intensity than individuals without dementia 12,13. A loss of awareness of pain has been reported by carers of patients with frontotemporal dementia (FTD).…”
Section: Introductionmentioning
confidence: 99%
“…An important issue that has barely been examined to date concerns the effect of dementia pathology on patients' responses to pain. For example, whereas patients with vascular dementia have been shown to report more pain compared to cognitively intact elderly controls [72,73], those two studies on patients with (frontal variant of) FTD suggest a decrease in pain in these patients, as was demonstrated by proxies' evaluations of patients' pain experience [74] as well as by a study showing increased pain threshold and tolerance levels in these patients [75]. Results in AD are more mixed, however, with some studies pointing to an increased pain reactivity [76] in these patients.…”
Section: The Impact Of Dementia Subtypementioning
confidence: 99%
“…Specific mental health conditions (e.g., depression, anxiety) and chronic sleep impairment have also been shown to predict subsequent cognitive decline and conversion to ADRD [13][14][15][16]. In addition, there is growing evidence from observational and experimental research that chronic pain, an increasingly common and highly burdensome condition, may also contribute to elevated risk for neurocognitive impairment and development of ADRD [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%